Atlas of health in Europe (WHO, 2003)
This statistical atlas presents key health figures for the WHO European Region. They cover basic demographic data, mortality and morbidity, lifestyles and environmental indicators such as alcohol consumption and road traffic accidents, and types and levels of health care. Most indicators are presented as a map to show overall regional variations, a bar chart to indicate country rankings and a time chart to show trends over time in three main country groupings. Using the WHO Regional Office for Europe's unique health for all database, combined with the best alternative sources of data around th.